Pelaksanaan Bimbingan Kelompok Dalam Meningkatkan Self-Regulation Siswa Di LPKA Kelas 1A Palembang - Maharani, Msy. Destri; Fauzi, Taty; Putri, Ramtia Darma (Universitas Nusantara PGRI Kediri, 2024)
The problem in this research concerns the low level of self-regulation of students assisted by Class 1 A Prison. In general, it is triggered by economic conditions and having an attitude of violating the law. The goal to be achieved is to find out whether group guidance services using Self-Management techniques can improve students' self-regulation at LPKA Class 1 Palembang. The research uses a quantitative approach with a treatment pre-experiment design, using a one group pretest-posttest design. Research subjects were Class IX of Filial Middle School Class 1 with a sample of 9 students. From 23 people the population was drawn based on total sampling technique. In accordance with the requirements, group guidance services take place. The data was tested using the Wilcoxon test, the results of the initial test and the final Asymp value test. Sig. (2-tailed = 0.006l < 0.05 hypothesis is accepted, there is a difference in the average results of the initial test and final test. The findings prove that there is a change in increasing students' self-regulation after receiving group guidance services using techniques through self-management.